Pengembangan Sistem Check-in Tamu Digital Berbasis Web untuk Monitoring Kunjungan pada Dinas Kominfo Kabupaten Tegal - Saputra, Rizqy Mulya; Wiyono, Slamet; Murtopo, Aang Alim; Syefudin, Syefudin (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Manual guest books in public offices often create incomplete visitor records, slow visit-history retrieval, weak host approval control, limited real-time visibility of active visitors, and difficulty in producing accountable reports. This study develops a web-based digital guest check-in system for monitoring visits at the Communication and Informatics Office of Tegal Regency. The research applies the waterfall model covering requirement analysis, system design, implementation, testing, and maintenance planning. The system includes guest self check-in, WhatsApp number validation, ID-card OCR assistance, host selection, host approval, visit status monitoring, in-app notification, Role-based Access Control, audit log, report export, and emergency attendance. The implementation uses Next.js 15, React, TypeScript, and Tailwind CSS on the frontend, NestJS on the backend, Socket.IO for realtime communication, and a relational data design prepared for PostgreSQL and Prisma ORM. Functional testing showed that login, guest check-in, form validation, OCR correction, approval, visit search, check-out, overstay marking, notification, reporting, user management, host management, endpoint handlers, and emergency attendance worked according to expected outputs. The developed system improves operational traceability, reduces dependence on paper records, strengthens role-based control, and provides faster visit information for front office, host, security, administrator, and leadership roles.